Pengaruh Penanganan Bagasi Rusak Terhadap Tingkat Kepuasan Penumpang Dari PT Kokapura Avia Di Bandar Udara Jenderal Ahmad Yani Semarang - Faishal Hilmy Fathurrachman; Hodi (Institut Nalanda, 2023)
Airline companies strive to improve their performance in order to satisfy the growing interest in air transportation. Aviation service quality focuses on safety, comfort, efficiency, and speed. The Lost and Found Baggage unit plays a crucial role in building trust. The risks associated with lost, delayed, or damaged baggage have a direct impact on passenger satisfaction. The success of this unit depends on prompt response, attention, effective communication, adherence to operational standards, and adequate assurance. It is imperative for companies to collaborate with airport managers and relevant stakeholders. This study adopts a quantitative approach, which is a scientific method that utilizes numerical data and statistics to explain and understand social or behavioral phenomena. The data collection techniques employed in this study include questionnaires and documentation. The data analysis techniques comprise simple linear regression analysis, t-tests, and the coefficient of determination. The results indicate that the handling of damaged baggage has a significant positive effect on passenger satisfaction at PT Kokapura Avia, Jenderal Ahmad Yani Airport, Semarang. The regression coefficient suggests that a 1% improvement in damaged baggage handling leads to a 0.784 increase in passenger satisfaction. This variable accounts for approximately 49.3% of the variance in passenger satisfaction. However, it is important to note that other factors contribute to satisfaction by 50.7% and warrant further research.